Au@MnSe2 Core–Shell Nanoagent Enabling Immediate Generation of Hydroxyl Radicals and Simultaneous Glutathione Deletion Free of Pre‐Reaction for Chemodynamic‐Photothermo‐Photocatalytic Therapy with Significant Immune Response. Issue 14 (4th May 2022) - Wang, Yuanlin; Sun, Xiang; Han, Yaqian; Wang, Kai; Cheng, Lixin; Sun, Ye; Besenbacher, Flemming; Yu, Miao
Abstract: As a typical tumor microenvironment‐responsive therapy, chemodynamic therapy (CDT), producing hydroxyl radicals ( OH) to eliminate tumor cells, has demonstrated great promise. Nevertheless, there are still major challenges: OH generated from endogenous H2 O2 is usually insufficient; the CDT effect is strongly dependent on the pre‐reaction with glutathione. Addressing the challenges, Au@MnSe2 core–shell nanoagent for synergetic chemodynamic‐photothermo‐photocatalytic therapy combined with tetramodal imaging, including magnetic resonance imaging, computed tomography, photoacoustic, and infrared thermal imaging is reported. Distinct from the reported glutathione‐depleting agents, Mn 2+ in MnSe2 allows immediate generation of OH, independent of pre‐reaction. Meanwhile, Mn 3+ consumes glutathione by its conversion to Mn 2+ . The Au‐MnSe2 combination promotes photothermal conversion and photocatalytic reaction, resulting in largely enhanced OH generation from endogenous H2 O2 and significant hyperthermia. Meanwhile, immune response is effectively activated: the intratumoral expression of programmed cell death‐1 and proinflammatory cytokines increase to 4–7 folds; the cytotoxic and helper T lymphocytes cells in the tumor area increase to more than 2.5‐folds; an evident, temporary systemic immunostimulatory effect is demonstrated. High tumor inhibition rate (≈97.3%) and greatly prolonged survival are obtained. This highly‐integrated design coordinating three different therapies with four different imaging modals provide new possibilities for high‐performance theranostic nanoagents. Abstract : Employing the Au@MnSe2 core–shell nanoagent, synergetic chemodynamic‐photothermo‐photocatalytic therapy with tetramodal imaging is realized. Distinct from the reported glutathione‐depleting agents, Mn 2+ in MnSe2 allows immediate generation of OH, independent of pre‐reaction. Besides the high OH generation efficiency from endogenous H2 O2 and hyperthermia, significant immune response is activated. High tumor inhibition rate and greatly prolonged survival are obtained.